Research morphological and anatomical structure of herb Cyperus esculentus (Cyperus esculentus L.) - I. M. Ivasiuk; S. M. Marchyshyn; L. I. Budniak (Zaporozhye State Medical University, 2019)
Cyperus esculentus (edible galingale, chufa, earth almond, tiger nutsedge) - Cyperus esculentus L. of the sedge family (Cyperaceae) today belongs to the new plant food resources used by mankind. This species can compete with traditional oilseed. In Ukraine, the Chufa culture has been known since the beginning of the XX century. The aim of the work is to study of the morphological and anatomical structure of the herb of the cyperus esculentus, suggested by the Department of New Cultures of the National Botanical Garden of the National Academy of Medical Sciences of Ukraine named after M. M. Hryshko, and establishing its main diagnostic features. Materials and methods. The micronutrients were made of the chufa leaves fixed in a mixture of alcohol-glycerol-water (1:1:1) and investigated by conventional methods using Item: PB-2610 microscope; the photo results were taken with a Samsung PL50 camera. Results. During microscopic studies of plant material, attention was paid to the morphological structure of the stem, leaf, epidermal cell structure, type of leaf blade, presence, number and type of stomata. Conclusions. The morphological and anatomical structure of the herb of the cyperus esculentus (chufa) was investigated. The main morphological features are triangular stem, linear structure, sessile, with vagina and parallel veins, without lingula and pubescence, thin, entire leaves. Generative shoots are occasionally formed. The main diagnostic anatomical features of the leaf of cyperus esculentus: bilaterally type leaf blade, hypostatic, fistucid. The upper (ventral) epidermis of a leaf of a plant is large-cell without stomata, the lower (dorsal) - small-celled with stomata; tetracitic type stomata; mesophyll is poorly differentiated, a large area is occupied by large expanses of thin-walled halo; in subepidermal layers numerous idioblasts with brownish-orange content are observed; among the base cells of the upper epidermis are groups of 6 motor transparent, substantially vacuolated or dead, devoid of chloroplasts, cells containing water, sometimes including small cubic crystals of calcium oxalate; conductive fascicule of collateral leaf vein, central larger than lateral, lateral fascicule varying in size, located below the upper epidermis and in the columnar regions of the parenchyma.